Pengaruh Perencanaan Pajak, Ukuran Perusahaan, Csr, Dan Gcg Terhadap Manajemen Laba - Almas Yunan (Yayasan Literasi Ilmiah Indonesia, 2023)
Purpose: This study aims to examine the influence of tax planning, company size, corporate social responsibility (CSR), and good corporate governance (GCG) on earnings management. Method: The study uses a sample obtained from manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2022, employing the purposive sampling method with a total sample of 38 companies and 190 annual financial reports. The method used in this research is multiple linear regression analysis to prove the influence of tax planning, company size, CSR, and GCG on earnings management. Finding: The results of this study indicate that tax planning has a positive influence on earnings management. Company size has a negative influence on earnings management. CSR has a positive influence on earnings management. GCG does not have a significant influence on earnings management. Novelty: This research is an update to the study conducted by Wardani & Santi (2018), with the addition of the GCG variable